MORPHOLOGICAL STUDY OF COMMUNICATION BETWEEN THE LONGITUDINAL STRIPS AND THE HUMAN CORPUS CALLOSUM - Boiagina, O. D. (International Journal of Medicine and Medical Research, 2017)
Background. It is established that there is an anatomical relationship between the corpus callosum and longitudinal strips. These formations must correlate to the common commissural system of the corpus callosum conductors. At present this issue in such a formulation is not considered in literature on Neuromorphology. Objective. The study was aimed to determine the commutations between the longitudinal strips and commissural conductors of the corpus callosum. Methods. The corpus callosum of people aged from 36 to 60 was studied. Some slices of the corpus callosum stem were used for impregnation and then inserted in paraffin blocks. Another part of these slices was subjected to plastination in epoxy resin. Results. Lateral longitudinal strips contain significantly greater mass of nerve conductors. Most of them compactly pass along limbic ring, while the other part is combined to nerve fibres of the corpus callosum commissural cords. The longitudinal strips are coated with an outer limiting glial membrane (grey coating). Conclusions. By means of the corpus callosum the connections between conscious and subconscious brain areas are structurally fixed. It can be assumed that longitudinal strips have relation to hippocampal area, related to the ancient formation of the pallium. This does not exclude the fact that the nerve fibres, found within longitudinal strips may have projections on the cortical cells of vaulted gyrus, which is considered to be paleopallium sphere. So, this interaction between the ancient and the old cortex should presumably be carried out by means of lateral longitudinal strips.